1997
DOI: 10.1111/j.1469-0691.1997.tb00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence and widespread dissemination of methicillin-resistant Staphylococcus aureus (MRSA) in hospitals in central Europe, with special reference to German hospitals

Abstract: OBJECTIVE: to present data on prevalence and interregional spread of methicillin-resistant Staphylococcus aureus (MRSA) in Germany. METHODS: A nationwide collection of MRSA isolates from nosocomial infections in 143 hospitals was established from isolates (n=4368) sent to a microbiological reference center during 1993--95. As chosen by distinguishable resistance phenotypes at each time of occurrence during the study period, 1830 isolates were subjected to molecular typing by means of Smal macrorestriction patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 16 publications
(20 reference statements)
4
61
0
5
Order By: Relevance
“…Besides having been detected in several countries (http://saureus.mlst.net), EMRSA-15 is replacing previous established clones in different regions of the world. In Europe, it was found in a number of hospitals throughout Germany (53), and it is currently established as the major clone in the Czech Republic (33) and in the Majorcan islands (7). A recent study performed in a hospital in Oporto, Portugal, showed that clone EMRSA-15, which might have been introduced in the hospital in 2001, represents the overwhelming majority (79%) of the isolates collected between 2003 and 2005 (8).…”
Section: Discussionmentioning
confidence: 99%
“…Besides having been detected in several countries (http://saureus.mlst.net), EMRSA-15 is replacing previous established clones in different regions of the world. In Europe, it was found in a number of hospitals throughout Germany (53), and it is currently established as the major clone in the Czech Republic (33) and in the Majorcan islands (7). A recent study performed in a hospital in Oporto, Portugal, showed that clone EMRSA-15, which might have been introduced in the hospital in 2001, represents the overwhelming majority (79%) of the isolates collected between 2003 and 2005 (8).…”
Section: Discussionmentioning
confidence: 99%
“…SmaI macrorestriction patterns were obtained as described previously (24). The CHEF-III apparatus from Bio-Rad (Munich, Germany) was used with the following conditions: a charge of 6 V/cm, pulse times of 5 to 15 s for 7 h and 15 to 60 s for 19 h, an angle of 120°, and a temperature of 14°C.…”
Section: Bacterial Isolatesmentioning
confidence: 99%
“…In England, the percentage increased from 1.5 to 13.2% between 1989 and 1995 (8)(9)(10)(11)(12)(13). In Brazil, the prevalence of MRSA is high, especially in large and teaching hospitals, ranging from 26.6 to 70%, and MRSA is considered to be the main pathogen causing hospital outbreaks (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%